2021
DOI: 10.1016/j.ccell.2021.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of cholangiocarcinoma growth by diverse cancer-associated fibroblast subpopulations

Abstract: In this study, Affo et al. determine origin and functions of cancer-associated fibroblasts in the liver and uncover distinct subsets that promote the growth of intrahepatic cholangiocarcinoma via different therapeutically targetable mediators. Upon publication of the original article, we realized that we had inadvertently omitted Dr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…The liver TME is composed of liver resident cells such as liver sinusoidal endothelial cells, HSCs, and Kupffer cells [35] and of other cell types such as myeloid-derived suppressor cells, regulatory T-cells, tumour-associated macrophages, and cancer-associated fibroblasts (CAFs) [39,40]. Recent studies have shown that HSCs are the major source of CAFs in liver cancer, although a small portion of the CAFs can be derived from other cell types, as shown in Figure 1 [9,41]. In conclusion, CAFs appear to be involved in every step of liver cancer development.…”
Section: Role Of Microenvironment In Liver Tumour Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The liver TME is composed of liver resident cells such as liver sinusoidal endothelial cells, HSCs, and Kupffer cells [35] and of other cell types such as myeloid-derived suppressor cells, regulatory T-cells, tumour-associated macrophages, and cancer-associated fibroblasts (CAFs) [39,40]. Recent studies have shown that HSCs are the major source of CAFs in liver cancer, although a small portion of the CAFs can be derived from other cell types, as shown in Figure 1 [9,41]. In conclusion, CAFs appear to be involved in every step of liver cancer development.…”
Section: Role Of Microenvironment In Liver Tumour Developmentmentioning
confidence: 99%
“…Because of the poor definition of CAFs, many researchers choose to use HSCs instead of CAFs when studying the role of fibroblasts in liver cancer (see sections 5 and 6). Recently, it was demonstrated that HSC-derived CAFs are essential for the production and remodelling of ECM in liver tumours [9,42]. An injured liver is characterized by the accumulation of ECM, which is composed of type I and III fibrillar collagens, fibronectin, undulin, laminin, hyaluronan, elastin, and proteoglycans [43].…”
Section: Definition and Use Of Cafs For In Vitro Liver Cancer Studiesmentioning
confidence: 99%
See 3 more Smart Citations